ANALISIS DAN RESENSI FILM MADAME X: DITINJAU DARI ANALISIS KRITIS KESETARAAN, STEREOTIP DAN IDEOLOGI DOMINAN - Rahmawati Zulfiningrum (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Queer refers to the concept of nomadic identity to oppose those who have afixed identity based on a binary sex gender system. The character of thecritical approach in Queer's theory suggests that power relations in societyare very important, especially when a person positions himself or herself inthe face of a marginalized society. Madame X's film reconstructs howminorities struggle to get their equal rights in society. This study uses areview method and literature from secondary data. The results of theanalysis show that the situation felt by the transsexual community in Indonesia is represented in this film, including the community's efforts toachieve equality in society. The category of comedy slapstick as the genreused in this film actually shows the superiority of heterosexuals overtranssexuals who are considered inferior. The initial mission of equalityfor the Queer that "everyone has the right to be happy, includingtranssexuals" is actually broken by the humor that is displayed.Transsexuals are still positioned as a minority, describe discriminatorytreatment, and establish stereotypes negative. The film also has varioussocial implications which can further support the dominant ideology.